Permanent Coma Patient Re-Learned to Speak via Coordination Dynamics Therapy - Schalow, Giselher (Archives of Clinical and Medical Case Reports, 2019)
Following an extreme severe brain injury in a car accident, a 22-year-old male patient lost approximate 50% of the brain and switched into the permanent coma state. One year after the accident coordination dynamics therapy (CDT) was started with 20 hours per week. Following 3 years of CDT he started to reach slowly the minimally consciousness state. Following 5 years of CDT, he was fully out-of-coma. Some movement functions re-appeared and he became able to communicate with the surrounding. Following 5.5 years of CDT he could move better and say the word ‘ma’ instead of mama. It was hoped that he could re-learn a few words. Through 5.7 years of intensive CDT, he rather suddenly became able to speak again. He could precisely repeat every word in English or Greek (mother tongue), but he was not able to have a conversation. The cognitive functions were still missing. Following 6 years of CDT the patient Manolis became able to exercise a bit on the special CDT device by himself. His higher mental functions, including memory, improved and he became able to communicate via speech. Because of the speeding up of the repair, when the patient was fully out-of-coma, more brain repair seems possible through further intensive CDT. It is discussed with respect to repair in spinal cord injury and cerebral palsy why such tremendous brain repair was possible.